Rendimento e qualidade de batata-doce em função de doses e fontes de K2O - Cardoso, Sará Santos (2018)
Sweet potato cultivation (Ipomoea batatas L.) has an important role in the agribusiness of vegetables in Paraíba and responds to the use of mineral fertilizers. Therefore, the objective of this research was evaluate the influence of doses and sources of K2O on yield and quality of sweet potato. The work was conducted between July and December 2017, at the Federal University of Paraíba, Areia-PB, Brazil, in a randomized block design in a 6 x 2 factorial arrangement with six doses of K2O (0, 50, 100, 150 , 200 and 250 kg ha-1) and two sources, chloride and potassium sulfate, with three replicates. The variables analyzed were: fresh and dry leaf masses, average commercial root mass, number and production of commercial roots plant -1, total and commercial root productivity, leaf N, P and K contents and starch content in roots. Potassium chloride was efficient to increase the fresh and dry leaf masses, the average mass of commercial roots and the production roots of commercial plant-1. Chloride and potassium sulphate sources increased the number of commercial roots plant-1. Potassium sulfate provided higher total root productivity in sweet potato, and commercial root productivities (24.67 and 26.50 t ha-1) were higher than the national average (12.4 t ha-1), when K2O was supplied of chloride and potassium sulphate, respectively. Foliar N and K contents were higher when potassium chloride and sulfate were used and the P content was higher with potassium chloride source, however, all nutrient contents were adequate for sweet potato. The maximum levels of starch in sweet potato were obtained with chloride and potassium sulphate. Chloride and potassium sulphate sources increased the productivity and quality of sweet potato roots.